1992
DOI: 10.2307/1389304
|View full text |Cite
|
Sign up to set email alerts
|

The Contours of Asian Professional, Technical and Kindred Work Immigration, 1965–1988

Abstract: This paper examines the nature of Asian professional, technical, and kindred (PTK) immigration to the United States since 1965. While many recent studies have noted the significant increase of Asian PTK immigration since 1965, analyses of who these PTKs are have been lacking. To address this omission, this paper focuses on three aspects of Asian PTK immigration: (1) the conditions underlying emigration from Asia; (2) the occupational composition of Asian PTKs; and (3) the impact of this immigration on understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Academic studies and U.S. public opinion polls, for instance, report negative perceptions of Latino immigrants (e.g., Burns and Gimpel 2000;Chavez 2008). By contrast, studies in the model minority myth research tradition argue that among immigrants, Asians are viewed as professionally successful and well-educated (Ho 2003;Kitano and Sue 1973;Liu 1992). By contrast, studies in the model minority myth research tradition argue that among immigrants, Asians are viewed as professionally successful and well-educated (Ho 2003;Kitano and Sue 1973;Liu 1992).…”
Section: Effect Of Foreign Citizenship On Labor Market Outcomesmentioning
confidence: 94%
“…Academic studies and U.S. public opinion polls, for instance, report negative perceptions of Latino immigrants (e.g., Burns and Gimpel 2000;Chavez 2008). By contrast, studies in the model minority myth research tradition argue that among immigrants, Asians are viewed as professionally successful and well-educated (Ho 2003;Kitano and Sue 1973;Liu 1992). By contrast, studies in the model minority myth research tradition argue that among immigrants, Asians are viewed as professionally successful and well-educated (Ho 2003;Kitano and Sue 1973;Liu 1992).…”
Section: Effect Of Foreign Citizenship On Labor Market Outcomesmentioning
confidence: 94%
“…On one hand, Burns and Gimple (2000) found that Americans generally hold negative perceptions of Latino immigrants, perhaps because they are viewed as lazy or maybe because they are seen as a threat to job opportunities. On the other hand, current beliefs held among Americans about recent Asian immigrants characterize them as being professional and well-educated (Ho 2003, Liu 1992.…”
Section: Country Of Origin As An Employment Cuementioning
confidence: 99%
“…These negative perceptions may also influence beliefs that recent Latin American immigrants are more likely to land in low-skilled jobs (Matoo et al 2007). On the other hand, beliefs that are held regarding Asian immigrants generally characterize them as being professional and well-educated (Ho 2003, Liu 1992). Lee and Fiske (2006) find that Asians are viewed as most competent, Canadians as moderately competent, and Mexican and Latino immigrants as possessing low competence.…”
Section: Country Of Origin As Employment Cuementioning
confidence: 99%